2007
DOI: 10.1007/s10577-007-1177-3
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome homology between mouse and three Muridae species, Millardia meltada, Acomys dimidiatus and Micromys minutus, and conserved chromosome segments in murid karyotypes

Abstract: Ryukyu spiny rats (genus Tokudaia) are indigenous species that are confined to three islands of the Nansei Shoto archipelago, Amami-Oshima, Tokunoshima and Okinawa-jima, Japan. Tokudaia tokunoshimensis from Tokunoshima Island and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The associations MMU5/9 and MMU5/10 are not exclusive to NLA as suggested by Hass et al [ 22 ], since MMU5/9 is found in Cricetulus griseus and Cricetus cricetus (Cricetidae: Cricetinae [ 40 , 46 ]), in Nannomys mattheyi (Muridae: Murinae; [ 44 ]) and Acomys dimidiatus (Muridae: Deomyinae; [ 38 ]); MMU5/10 in NLA is also shared by Ellobius lutescens , Ellobius talpinus , Microtus agrestis and Microtus oeconomus (Cricetidae: Arvicolinae, [ 41 42 ]; S2 Table ). In addition, MMU5/7 is not shared only by N .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The associations MMU5/9 and MMU5/10 are not exclusive to NLA as suggested by Hass et al [ 22 ], since MMU5/9 is found in Cricetulus griseus and Cricetus cricetus (Cricetidae: Cricetinae [ 40 , 46 ]), in Nannomys mattheyi (Muridae: Murinae; [ 44 ]) and Acomys dimidiatus (Muridae: Deomyinae; [ 38 ]); MMU5/10 in NLA is also shared by Ellobius lutescens , Ellobius talpinus , Microtus agrestis and Microtus oeconomus (Cricetidae: Arvicolinae, [ 41 42 ]; S2 Table ). In addition, MMU5/7 is not shared only by N .…”
Section: Discussionmentioning
confidence: 85%
“…The association MMU5/9 is shared among three Cricetidae ( N . lasiurus , Cricetulus griseus and Cricetus cricetus ; [ 22 , 40 , 45 46 ]), two Muridae ( Nannomys mattheyi [ 44 ] and Acomys dimidiatus [ 38 ]; S2 Table ). The association MMU5/10 is shared with NLA and four Arvicolinae species ( Ellobius lutescens , Ellobius talpinus , Microtus agrestis and Microtus oeconomus ; [ 41 42 ]; S2 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Distinct dark centromeric C-bands occur on all chromosomes, and some of them possess the C-heterochromatic short arms (see Zima 1983a, Zima & Král 1984b, Lungeanu et al 1986and Schmid et al 1984 for review of chromosome banding studies). Cross-species chromosome painting was applied in this species by Nakamura et al (2007) and Lin et al (2013). The conventionally stained karyotype of the Turkish population was studied by Özkan et al (2003) in Thrace and a standard complement was found.…”
Section: Iranian Vole Microtus Iranimentioning
confidence: 99%